2022
DOI: 10.3389/fcvm.2022.943229
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of CatLet© angiographic scoring system for long-term prognosis in patients with acute myocardial infarction presenting > 12 h after symptom onset

Abstract: BackgroundWe have recently developed the Coronary Artery Tree description and Lesion EvaluaTion (CatLet©) angiographic scoring system, which is capable of accounting for the variability in coronary anatomy, and risk-stratifying patients with coronary artery disease. This study aimed to clarify whether the CatLet score had a predictive value for long-term prognosis in patients with acute myocardial infarction (AMI) presenting > 12 h after symptom onset.Materials and methodsThe CatLet score was calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In the Kaplan-Meiere analysis, patients in the CatLetmid and in the CatLettop were associated with hazard ratios (95% CI) 1.68 (1.15–2.44)-fold, and 3.59 (2.56–5.03)-fold increased risk of MACEs, respectively. The discriminations and calibrations of the CatLet or Hexu score for MACEs were also good ( 7 ). We also investigated the reproducibility of the CatLet or Hexu angiographic scoring system.…”
Section: Available Studies On the Catlet Or Hexu Angiographic Scoring...mentioning
confidence: 99%
“…In the Kaplan-Meiere analysis, patients in the CatLetmid and in the CatLettop were associated with hazard ratios (95% CI) 1.68 (1.15–2.44)-fold, and 3.59 (2.56–5.03)-fold increased risk of MACEs, respectively. The discriminations and calibrations of the CatLet or Hexu score for MACEs were also good ( 7 ). We also investigated the reproducibility of the CatLet or Hexu angiographic scoring system.…”
Section: Available Studies On the Catlet Or Hexu Angiographic Scoring...mentioning
confidence: 99%
“…The CatLet extended validation trial (ChiCTR2000033730) and the CatLet validation trial (ChiCTR-POC-17013536), both being registered with chictr.org, served as the derivation and validation datasets, respectively [7,8]. All the participants, aged ≥18 years, homogeneous in Chinese Han ethnicity, were consecutively enrolled.…”
Section: Study Populationmentioning
confidence: 99%
“…[ 13 ] We have recently developed a new Coronary Artery Tree description and Lesion EvaluaTion (CatLet) angiographic scoring system. [ 14 ] Our preliminary studies demonstrated that this novel angiographic scoring system was better than the SYNTAX score to account for the variability in the coronary anatomy, to evaluate the severity and the complexity of diseased coronary artery trees, and to predict clinical outcomes for AMI patients, [ 15 , 16 ] with high reproducibility. [ 17 ] Our prior study also demonstrated that the predictive value of the CatLet score could be improved through a combination with age, serum creatinine, and left ventricular ejection fraction (LVEF).…”
Section: Introductionmentioning
confidence: 99%